Trust in Technology Sebagai Mediasi Pengaruh Ease of Transaction dan Halal Digital Lifestyle Terhadap Penggunaan QRIS - Nurdiana Putri; Peni Haryanti (DPPM Universitas Pelita Bangsa, 2025)
This study aims to analyze trust in technology as a mediator of the influence of ease of transaction and halal digital lifestyle on the use of QRIS. A total of 100 students from Hasyim Asy'ari University (UNHASY) were used as respondents in this study, who were randomly selected using the random sampling method. The approach used is quantitative with a causal associative research design. Data collection was carried out using a questionnaire instrument, then analyzed using the PLS-SEM approach, with an outer model evaluation including validity and reliability tests, and an inner model evaluation through a path coefficient test consisting of direct, indirect, and coefficient of determinants (R2). Based on the results of the analysis, it is known that ease of transaction has a significant effect on trust in technology, halal digital lifestyle has a significant effect on trust in technology, and trust in technology has a significant effect on the use of QRIS. In addition, trust in technology is proven to mediate the influence of ease of transaction and halal digital lifestyle on the use of QRIS.